Dosing Guidance for Intravenous Colistin in Critically Ill Patients - Nation, Roger L.; Garonzik, Samira M.; Thamlikitkul, Visanu; Giamarellos-Bourboulis, Evangelos J.; Forrest, Alan; Paterson, David L.; Li, Jian; Silveira, Fernanda P. (Clinical infectious diseases, 2017)
Background. Intravenous colistin is difficult to use because plasma concentrations for antibacterial effect overlap those causing nephrotoxicity, and there is large interpatient variability in pharmacokinetics. The aim was to develop dosing algorithms for achievement of a clinically desirable average steady-state plasma colistin concentration (Css,avg) of 2 mg/L. Methods. Plasma concentration-time data from 214 adult critically ill patients (creatinine clearance, 0–236 mL/min; 29 receiving renal replacement therapy [RRT]) were subjected to population pharmacokinetic analysis. Development of an algorithm for patients not receiving RRT was based on the relationship between the dose of colistimethate that would be needed to achieve a desired Css,avg and creatinine clearance. The increase in colistin clearance when patients were receiving RRT was determined from the population analysis and guided the supplemental dosing needed. To balance potential antibacterial benefit against risk of nephrotoxicity the algorithms were designed to achieve target attainment rates of >80% for Css,avg ≥2 and <30% for Css,avg ≥4 mg/L. Results. When algorithm doses were applied back to individual patients not receiving RRT (including those prescribed intermittent dialysis on a nondialysis day), >80% of patients with creatinine clearance <80 mL/min achieved Css,avg ≥2 mg/L, but for patients with creatinine clearance ≥80 mL/min, the target attainment was <40%, even with the maximum allowed daily dose of 360 mg colistin base activity. For patients receiving RRT, target attainment rates were >80% with the proposed supplemental dosing. In all categories of patients, <30% of patients attained Css,avg ≥4 mg/L. Conclusions. The project has generated clinician-friendly dosing algorithms and pointed to circumstances in which intravenous monotherapy may be inadequate.